PENGEMBANGAN DESAIN PRODUK TAS SELEMPANG WANITA BERBAHAN DASAR ECENG GONDOK - Noerrohman, Dendi; Sirait, Ganda (Computer Science and Industrial Engineering, 2023)
The water hyacinth plant is a type of aquatic plant flora that is considered a weed or pest because of the damage it does to water systems and the water supply. To a large extent, reservoirs with an influx of garbage are to blame for the rapid expansion of water hyacinth. Water hyacinth has a rapid growth rate at Batam City's Duriangkang reservoir. The hyacinth population will double in size in a couple of days. Ultimately, this study aims to inform the creation of a cutting-edge bag style made from water hyacinth. Research suggests that asking a representative sample of young people what kinds of bag products they would be interested in buying would be the best method to inform the design of a bag product catering to the needs of this demographic. Based on the survey data collected, a plan of action is developed for manufacturing bag products that both meet consumer demand and stay within budget. This plan calls for the use of low-cost raw materials without sacrificing quality, such as water hyacinth, which can be obtained in large quantities